Huntingdonshire introduction - Thorn, Caroline; Thorn, Frank (The University of Hull)
The introduction discusses the geography and history of the county; the county boundary; Hidage; the Hundreds, their names, arrangements, boundaries, lordship, moot-sites, courts, and later Hundreds; the administration of the county; manorial and ecclesiastical organisation; the state of the manuscript for the county; amendments to the text; the Declarations; Lordship land; the rubrication of the Hundreds, Hundred and Vill order, borough and castle; related or 'satellite' texts; the "Inquisitio Eliensis" (Ely Enquiry); the editorial history of earlier versions of the notes, and the current state of the revision. The introduction has been written for this edition by Caroline and Frank Thorn.